2012
DOI: 10.5194/aab-55-626-2012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tonic immobility in common pheasant hens kept in different housing systems during laying period

Abstract: Common pheasant (Phasianus colchicus) hens kept in different housing systems during laying period were exposed to a tonic immobility test. At the end of the laying period, the shortest duration of the tonic immobility, and thus the lowest fear level, was found in birds kept in enriched cages, i.e. cages equipped with 2 perches and a hiding place. The duration of the tonic immobility in hens kept in enriched cages was significantly lower (P<0.05) than in hens kept in conventional cages where other measures agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Stressful conditions in early life may increase susceptibility to disease. Pheasants reared in barren conditions exhibited higher levels of tonic immobility, indicative of stress, than those reared in enhanced conditions (Hrabcakova et al 2012). High-density releases may provoke competition and restrict access to resources such as water and shelter, which facilitates the effects of pheasant coronavirus and causes kidney failure precipitated later by chilling and water deprivation (Pennycott 2000).…”
Section: Factors That Exacerbate Disease Levels In Released Birdsmentioning
confidence: 99%
“…Stressful conditions in early life may increase susceptibility to disease. Pheasants reared in barren conditions exhibited higher levels of tonic immobility, indicative of stress, than those reared in enhanced conditions (Hrabcakova et al 2012). High-density releases may provoke competition and restrict access to resources such as water and shelter, which facilitates the effects of pheasant coronavirus and causes kidney failure precipitated later by chilling and water deprivation (Pennycott 2000).…”
Section: Factors That Exacerbate Disease Levels In Released Birdsmentioning
confidence: 99%
“…Furthermore, commercial pheasant rearing has developed as an alternative poultry sector for meat production (Kececi and Col 2010, Hrabcakova et al 2012, Nazifi et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…A study on breeding pheasants showed that sight barriers may improve welfare by reducing potentially harmful aggressive interactions (Deeming et al 2011). Laying pheasant hens kept in enriched cages (with perches and a hiding place) were less stressed and fearful than pheasants kept in conventional cages (Hrabcakova et al 2012). Recently Whiteside et al (2016) showed that the enrichment of rearing habitats of pheasants during the first weeks of life, achieved by adding elevated perches, provoked an interrelated suite of morphological, cognitive and behavioural changes, culminating in decreased mortality of birds after their release in the wild.…”
Section: Introductionmentioning
confidence: 99%